The Influence of Brand Ambassadors, Halal Labeling, and Price on Purchase Decisions of Wardah Skincare Products Among Generation Z in Medan - Maya Almalia Azhari; Alim Murtani (AHKAM, 2025)
This study investigates the influence of brand ambassadors, halal labeling, and price on the purchase decisions of Wardah skincare products among Generation Z consumers in Medan City. Consumer purchase decisions involve the processes of selecting, acquiring, and using products or services to fulfill individual needs and preferences. Employing a quantitative research design with a causal associative approach, this study utilized cross-sectional primary data collected through a structured questionnaire. The target population comprised Generation Z individuals in Medan who have purchased and used Wardah skincare products, with a randomly selected sample of 100 respondents. The results of the analysis reveal that the brand ambassador variable has a significant partial effect on purchase decisions (t = 3.485, p = 0.001). Similarly, halal labeling shows a significant partial influence (t = 2.411, p = 0.018), as does price (t = 3.414, p = 0.001). Furthermore, the three variables collectively exert a significant influence on purchase decisions (F = 30.025, p = 0.000). These findings highlight the importance of ethical branding, religious considerations, and pricing strategies in shaping consumer behavior, particularly among Gen Z consumers in a predominantly Muslim market.